Edukacja pozaszkolna dzieci – zmienić myślenie o przyszłości - Kasprzak, Michalina (Studia Edukacyjne, 2016)
Non-formal education is undervalued nowadays. The importance of education establishments is greater for children and young people who come from families with a lower socioeconomic status. In this paper I would like to present the potential and possible changes of Free Educational Centres for children with a lower socioeconomic status. Children using additional educational institutions free of charge can get the chance for a better future.